Bishop Equations of Smarandache TM1 Curves of Biharinonic B-Slant Helices in Heis3 - Korpinar, Talat; Turhan, Essin (Soc Paranaense Matematica, 2014)
In this paper, we study Bishop equations for Smarandache TM1 curves of biharmonic B-slant helices according to Bishop frame in the Heisenberg group Heis(3). Finally, we characterize the Smarandache TM1 curves of biharmonic, B-slant helices in terms of Bishop frame in the Heisenberg group Heis(3).
Keywords: Biharmonic curve; Bishop frame; Heisenberg group